(3bWYI aj GdJaSjQs
(3ChdgG (B:s
(3ef MWGe GdOfjG GdYXjeI GdhRf YfO CgdgG bhdg Ld hYR (B( (3bd ef cGf YOh dLHQjd , aEfg fRdg Ydi bdHc(B) (3hceG CNHQ Gddg JYGdi Yf MQUge Ydi GdMjGI GdOfjG s
(3BNQgG (B:s
(3hbO bjd Cf GdSMQ bO jchf ai GdNjGd hbO jchf ai GdCYjGf ceG ai GdNjGd hbhdg JYGdi (B( (3ajJYdehf efgeG (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs